Analisis Berpikir Pseudo Siswa IQ Normal dalam Pemecahan Masalah Matematika - Tri Swaraswati; Teguh Wibowo; Riawan Yudi Purwoko (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
This study aims to describe the occurrence of pseudo thinking of high school students who have a normal IQ in solving the mathematical problems in the material Position and Distance from Point, Line, and Field. This research is a qualitative study with a phenomenological approach. Data were collected by through giving tests and verification with interviews. The subject is taken using the snowball technique. The research subjects were students who had a normal IQ (80-119). Where subject who have a normal IQ in this research are two students. The data analysis techniques used is data reduction, data presentation, and conclusion. Based on the results of the analysis it was found that high school students with normal IQ have a low understanding of the concepts in Geometry (Position and Distance from Points, Line, and Fields).